Method for preparing component-adjustable multi-element nano alloy powder coated with controllable carbon structure by adopting plasma

By using a ocene-based metallic compound in plasma reaction without the need for an additional carbon source to generate carbon-coated nanoalloy powder, the problems of complex synthesis methods and single product structure in the prior art are solved, and rapid and controllable nanoalloy powder preparation is achieved, with wide application prospects.

CN119794369AActive Publication Date: 2025-04-11BEIJING UNIV OF TECH +1
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202510119471.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-11
Estimated Expiration
2045-01-24

AI Technical Summary

Technical Problem

The existing synthetic methods of carbon-coated nanometal particles are complex, have a long production cycle, high manufacturing cost, and a single product structure, making it difficult to regulate carbon content and structure.

Method used

Using a metallocene compound as the only raw material, carbon-coated nanoalloy powder with controllable carbon content and structure, controllable metal core crystallinity, and adjustable alloy composition through plasma reaction without the need for additional carbon source.

Benefits of technology

It has achieved rapid preparation of carbon-coated nano alloy powder, with small particle size, good spherical shape, good electrical, magnetic properties and chemical stability, and is suitable for catalysis, electromagnetic wave absorption, electromagnetic shielding and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119794369A_ABST
    Figure CN119794369A_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing component-adjustable multi-element nano alloy powder coated with a controllable carbon structure by adopting plasma. The powder has a coating structure, a coating layer is composed of one or two of amorphous carbon or graphite, and the thickness of the coating layer is 5-50 nm; the core is an alloy particle, and the particle size range is 5-200nm. The sublimable metallocene metal compound is used as a carbon source and a metal source, plasma is used as a synthesis environment, reactant toxicity and environmental pollution are reduced, the preparation speed is high, and mass production is facilitated. The carbon-coated nano-alloy powder with controllable carbon content, controllable structure, controllable crystallinity and controllable alloy components can be prepared by regulating and controlling the power of a plasma generator, the residence time of a carrier gas in a plasma region and the flow of the carrier gas.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nano functional powder materials and powder preparation, and specifically relates to a multi-component nano alloy powder with adjustable components coated with a controllable carbon structure and a preparation method thereof. Background Art

[0002] Metal nanomagnetic particles are widely used in catalysis, batteries, sensors, powder metallurgy, magnetic fluids and other fields due to their excellent magnetism and electrical conductivity. However, due to their exposure to air and water, they are very susceptible to oxidation, resulting in performance degradation. Graphene is a single-layer material composed of carbon atoms arranged in a honeycomb structure, with excellent electrical conductivity, thermal conductivity, mechanical strength and chemical stability. Therefore, the composite material formed by carbon-coated metal nanoparticles can improve its electrical conductivity, thermal conductivity and mechanical properties, and can effectively prevent the oxidation of nanometal particles. This composite material can be well used in electromagnetic shielding materials, electromagnetic wave absorption materials, sewage treatment, catalysis, battery electrodes, magnetic fluids and other fields.

[0003] At present, the synthesis methods of carbon-coated nanometal particles mainly include chemical vapor deposition, pyrolysis, arc discharge, etc. In these methods, carbon sources and reducing substances must be used to help carbon grow on metal powders, and the carbon content, carbon structure, and crystallinity of the products cannot be regulated.

[0004] The application publication number is CN1161973595A, the publication date is June 2, 2023, and the patent name is: A method for preparing graphene-coated metal nanoparticles. It invents a method for preparing graphene-coated metal nanoparticles, which uses tartrate metal as a raw material and pyrolyzes it at high temperature to obtain graphene-coated metal nanoparticles.

[0005] The application publication number is CN114572971A, the publication date is June 3, 2022, and the patent name is: A method for preparing graphene on the surface of copper powder. It invented a method for coating graphene on the surface of copper powder, which uses methane as the carbon source and calcines at high temperature to obtain graphene-coated copper powder.

[0006] The application publication number is CN11103248A, the publication date is May 29, 2020, and the patent name is: A method for preparing doped graphene-coated transition metal carbide nanocapsules and their application in microwave catalysis. The method is prepared by placing a metal block on a DC arc plasma device, introducing hydrogen, inert gas, carbon-containing gas, etc., and then evaporating the metal through a DC arc, and forming graphene-coated metal carbide nanocapsules after cooling.

[0007] The above methods all have their own advantages, but are also accompanied by many problems, such as complex preparation process, long production cycle, high manufacturing cost, high risk of gas source used, single product structure, etc., which affect the production and application of carbon-coated metal nanoparticles. Summary of the invention

[0008] In view of the problems existing in the above-mentioned background technology, the present invention aims to provide a new method for preparing carbon-coated nano-alloy powder.

[0009] In the present invention, when the metallocene compound is the only raw material, it is sublimated and then brought into the plasma reaction chamber in the form of a carrier gas, without adding an additional carbon source, so that carbon-coated nano alloy powders with controllable carbon content and structure, controllable metal core crystallinity, and controllable alloy composition can be quickly generated in one step.

[0010] The technical principle of the present invention is:

[0011] Taking advantage of the easy sublimation property of the metallocene compound, it is first sublimated into a gas in a heating chamber, and then ammonia is introduced to bring the metallocene compound vapor into the plasma reaction chamber. Under the action of the plasma, the chemical bonds of the metallocene compound are broken and become C atoms, H atoms, CH x The metal carbon compounds gather in large quantities to form nanocrystalline nuclei. During the cooling process, due to the large temperature difference between the inside and outside of the particles, C gradually precipitates from the inside to form a coating layer. After cooling, carbon-coated nano alloy powders are obtained.

[0012] There are energy differences in the process of different free radicals decomposing and releasing H free radicals in the NH3 plasma flow. The ion state of NH3 plasma can be controlled by controlling the power of the plasma generator. NH2+e - →NH+H+e - NH+e - →N+H+e - NH3, NH2 and NH free radicals release H free radicals through collision dissociation, and the H free radicals react with CH x The free radicals and C free radicals form stable CH compounds and are discharged in the form of gas, thereby controlling the C content and structure in the product;

[0013] The residence time t of the carrier gas flow in the plasma region is controlled by controlling the plasma region length L and the gas flow Q. L-plasma region length, Q-carrier gas flow rate, A-inlet pipe cross-sectional area) to achieve product core crystallinity control;

[0014] The molar ratio of the metallocene compound entering the plasma reaction area per unit time is controlled by controlling the flow rate of the carrier gas, so as to achieve adjustable product composition. For example, in Example 2, the ammonia flow rate of the ferrocene fluidized bed is 2 slpm (liters / minute), and the ammonia flow rate of the nickelocene ferrocene fluidized bed is 2 slpm, and the product has an Fe:Ni atomic ratio of 1:1, that is, the metal core is FeNi.

[0015] To achieve the above object, the technical solution of the present invention is as follows:

[0016] Step 1: Evacuate the plasma reaction chamber and fill it with nitrogen. Then evacuate the chamber and fill it with argon until the argon fills the entire reaction chamber to 10 5 Pa, isolated from air;

[0017] Step 2: introducing ammonia gas to adjust the ammonia partial pressure, and connecting the plasma generator power supply to excite and obtain a stable ammonia plasma flow;

[0018] Step 3: subliming the metallocene compound in a plurality of sublimation chambers respectively;

[0019] Step 4: introducing ammonia gas into the sublimation chamber respectively, adjusting the ammonia gas flow rate, and sending the metallocene compound vapor into the plasma region through the ammonia gas;

[0020] Step 5: Adjust the plasma generator power and the length of the plasma region;

[0021] Step 6: The metallocene compound vapor and ammonia begin to react in the plasma reactor at a set power and zone length to generate carbon-coated nano alloy powder;

[0022] Step 6: Cool the reaction chamber to room temperature under ammonia protection conditions, and collect the obtained powder, which is the carbon-coated nano alloy powder.

[0023] Among them, the metallocene compound used: ferrocene (C 10 H 10 Fe), nickelocene (C 10 H 10 Ni), cobaltocene (C 10 H 10 Co) and manganese cyclopentadienyl (C 10 H 10 Mn) as a metal source and a carbon source.

[0024] Further, the temperature of the ferrocene sublimation chamber is set to 100-160°C, the temperature of the nickelocene sublimation chamber is set to 120-160°C, the temperature of the cobaltocene sublimation chamber is set to 40-100°C, and the temperature of the manganeseocene sublimation chamber is set to 110-150°C, the carrier gas is ammonia, and the gas flow Q is adjustable.

[0025] Among them, by controlling the flow rate of the carrier gas to control the molar ratio of the metallocene compound entering the plasma reaction area per unit time, A, B, C, D represent Fe, Co, Ni, Mn elements respectively, and x, y, z, p represent the molar fraction of each component respectively. The chemical formula is A x B y C z D p , wherein x+y+z+p=1, x,y,z,p≥0 and at least any two variables>0, the alloy core finally realizes the adjustable phase and continuous adjustable composition of the alloy core. For example, in Example 2, the ammonia gas flow rate of the ferrocene fluidized bed is 2slpm (liters / minute), the ammonia gas flow rate of the nickelocene ferrocene fluidized bed is 2slpm, and the product has a Fe:Ni atomic ratio of 1:1, that is, the metal core is FeNi. .

[0026] Among them, the plasma generator type includes one or more of inductively coupled plasma, microwave coupled plasma, and capacitively coupled plasma, the generator power is adjustable, and the plasma effective area in the reaction chamber is adjustable.

[0027] Furthermore, the residence time t of the carrier gas flow in the plasma region is controlled by controlling the plasma region length L and the gas flow Q. L-plasma zone length, Q-carrier gas flow rate, A-inlet pipe cross-sectional area) to achieve control of the crystallinity of the product core.

[0028] Furthermore, the ion state of NH3 plasma is controlled by adjusting the power of the plasma generator. NH2+e - →NH+H+e - NH+e - →N+H+e - NH3, NH2 and NH free radicals release H free radicals through collision dissociation, and the H free radicals react with CH x The free radicals and C free radicals form stable CH compounds and are discharged in the form of gas, thereby controlling the carbon content and structure in the product.

[0029] The advantages of the present invention are:

[0030] (1) Using metallocene compounds as metal sources and carbon sources and plasma as the reaction environment can reduce the pollution caused by the reactants. There is no need to add additional carbon source gas, which makes the experiment safer and conducive to mass production.

[0031] (2) During the preparation process, the molar ratio of the metallocene compound entering the plasma reaction area per unit time is controlled by adjusting the flow rate of the carrier gas, so that binary, ternary, and quaternary carbon-coated nano-alloy powders with different components and contents can be obtained.

[0032] (3) During the preparation process, the crystallinity of the metal core can be regulated by adjusting the length of the plasma region to control the residence time of the gas flow in the plasma region.

[0033] (4) During the preparation process, the carbon content and structure can be controlled by adjusting the power of the plasma generator to control the degree of carrier gas decomposition.

[0034] (5) The carbon-coated nano-alloy powder prepared by the method of the present invention has a small and uniform particle size, good sphericity, and a simple and fast preparation process.

[0035] (6) The carbon-coated nanopowder particles prepared by the method of the present invention have good electrical properties, magnetic properties and chemical stability, and have broad application prospects in the fields of catalysis, electromagnetic wave absorption, electromagnetic wave shielding, battery electrodes, magnetic fluids, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 These are the XRD and TEM images of the carbon-coated nano-alloy powder prepared in Example 1.

[0037] Figure 2 These are the XRD and TEM images of the carbon-coated nano-alloy powder prepared in Example 2.

[0038] Figure 3 These are the XRD and TEM images of the carbon-coated nano-alloy powder prepared in Example 3.

[0039] Figure 4 These are the XRD and TEM images of the carbon-coated nano-alloy powder prepared in Example 4.

[0040] Figure 5 These are the XRD and TEM images of the carbon-coated nano-alloy powder prepared in Example 5.

[0041] Figure 6 Schematic diagram of a plasma reaction device with controllable plasma region length DETAILED DESCRIPTION

[0042] The present invention will be further described below in conjunction with the embodiments and drawings, but they should not be construed as limiting the present invention.

[0043] The method for preparing a multi-element nano alloy powder coated with a controllable carbon structure and adjustable composition provided by the present invention comprises the following steps:

[0044] After the plasma reaction chamber is evacuated, nitrogen is filled in, and then argon is filled in after the evacuation operation until the argon fills the entire reaction chamber to 10 5 Pa, isolated from air;

[0045] Ammonia gas is introduced to adjust the partial pressure of ammonia gas, and a plasma generator power supply is turned on to excite and obtain a stable ammonia plasma flow;

[0046] subliming the metallocene compound in a plurality of sublimation chambers respectively;

[0047] The metallocene compound vapor and ammonia begin to react in a plasma reactor at a set power and zone length to generate carbon-coated nano alloy powder;

[0048] Ammonia gas is introduced into the sublimation chamber respectively, and the gas flow rate of ammonia gas is adjusted to deliver the vapor of metallocene compound into the plasma region through the ammonia gas;

[0049] Adjusting the plasma generator power and the length of the plasma zone;

[0050] The reaction chamber is cooled to room temperature under the protection of ammonia gas, and the obtained powder is collected, which is the carbon-coated nano alloy powder.

[0051] The device used may be an existing plasma generating device. In the embodiment, the device disclosed in patent CN104851548A is specifically used.

[0052] The specific preparation process of the carbon-coated nano alloy powder in the embodiment is as follows:

[0053] Embodiment 1:

[0054] Using ferrocene and nickelocene as raw materials, the plasma reaction chamber was evacuated and then filled with nitrogen. After evacuation, argon was filled until the argon filled the entire reaction chamber to 10 5 Pa, isolated from air. The power of the first plasma generator was set to 3kW, the power of the second plasma generator was set to 0kW, and the power of the third plasma generator was set to 0kW. The total power was 3kW, and ammonia was used to excite stable ammonia plasma. At this time, the effective reaction length of the airflow through the plasma area was 10cm. The temperature of the ferrocene sublimation chamber was set to 130℃, and the temperature of the nickelocene sublimation chamber was set to 150℃. 2slpm ammonia was introduced into the ferrocene fluidized bed, and 1.125slpm ammonia was introduced into the nickelocene fluidized bed. The vapors of both were brought into the plasma flame, and carbon-coated nano-Fe was obtained after plasma reaction. 0.64 Ni 0.36 Alloy powder, the XRD pattern of the product is as follows Figure 1 (a) shows the TEM image. Figure 1 As shown in (b) and (c).

[0055] Depend on Figure 1 As shown in (a), the product prepared in Example 1 is composed of carbon and Fe 0.64 Ni 0.36 Composed of. Figure 1 (b) and (c) show that the product has an obvious coating structure, with an amorphous carbon layer covering the core. The core interplanar spacing was measured to be about 0.207 nm, which is consistent with the Fe 0.64 Ni 0.36 The (111) crystal plane spacing is close, which is consistent with the XRD data. The XRD diffraction peak intensity is low and the diffraction peak is wide, which proves that the prepared carbon-coated Fe 0.64 Ni 0.36 Low crystallinity.

[0056] Embodiment 2:

[0057] Using ferrocene and nickelocene as raw materials, the plasma reaction chamber was evacuated and then filled with nitrogen. After evacuation, argon was filled until the argon filled the entire reaction chamber to 10 5 Pa, isolated from the air. The power of the first plasma generator was set to 3kW, the power of the second plasma generator was set to 0kW, and the power of the third plasma generator was set to 0kW. The total power was 3kW, and ammonia was used to excite stable ammonia plasma. At this time, the effective reaction length of the airflow through the plasma area was 10cm. The temperature of the ferrocene sublimation chamber was set to 130°C, and the temperature of the nickelocene sublimation chamber was set to 150°C. 2slpm of ammonia was introduced into the two sublimation chambers to bring ferrocene and nickelocene vapor into the plasma flame. After the plasma reaction, carbon-coated nano-FeNi alloy powder was obtained. The XRD pattern of the product is shown in the figure. Figure 2 (a) shows the TEM image. Figure 2 As shown in (b) and (c).

[0058] Depend on Figure 2 As shown in (a), the product phase prepared in Example 2 is composed of carbon and FeNi. Figure 2 (b) and (c) show that the prepared product has an obvious coating structure, and the core is coated with an amorphous carbon layer.

[0059] Embodiment 3:

[0060] Using ferrocene and nickelocene as raw materials, the plasma reaction chamber was evacuated and then filled with nitrogen. After evacuation, argon was filled until the argon filled the entire reaction chamber to 10 5Pa, isolated from the air. The power of the first plasma generator was set to 3kW, the power of the second plasma generator was set to 0kW, and the power of the third plasma generator was set to 0kW. The total power was 3kW, and ammonia was used to excite stable ammonia plasma. At this time, the effective reaction length of the airflow through the plasma area was 10cm. The temperature of the ferrocene sublimation chamber was set to 130°C, and the temperature of the nickelocene sublimation chamber was set to 150°C. 2slpm of ammonia was introduced into the ferrocene fluidized bed, and 6slpm of ammonia was introduced into the nickelocene fluidized bed. The vapors of both were brought into the plasma flame. After the plasma reaction, carbon-coated nano-FeNi3 alloy powder was obtained. The XRD pattern of the product is shown in the figure. Figure 3 (a) shows the TEM image. Figure 3 As shown in (b) and (c).

[0061] Depend on Figure 3 As shown in (a), the product phase prepared in Example 3 is composed of carbon and FeNi3. Figure 3 (b) and (c) show that the prepared product has an obvious coating structure, and the core is coated with an amorphous carbon layer.

[0062] Embodiment 4:

[0063] Using ferrocene and nickelocene as raw materials, the plasma reaction chamber was evacuated and then filled with nitrogen. After evacuation, argon was filled until the argon filled the entire reaction chamber to 10 5 Pa, isolated from the air. The power of the first plasma generator was set to 4.5kW, the power of the second plasma generator was set to 4.5kW, the power of the third plasma generator was set to 4.5kW, and the total power was 13.5kW. Ammonia was used to excite stable ammonia plasma. At this time, the effective reaction length of the gas flow through the plasma was 30cm. The temperature of the ferrocene sublimation chamber was set to 130°C, and the temperature of the nickelocene sublimation chamber was set to 150°C. 2slpm of ammonia was introduced into the two sublimation chambers to bring ferrocene and nickelocene vapor into the plasma flame. After the plasma reaction, carbon-coated nano-FeNi alloy powder was obtained. The XRD pattern of the product is shown in the figure. Figure 4 (a) shows the TEM image. Figure 4 As shown in (b) and (c).

[0064] Depend on Figure 4 As shown in (a), the product phase prepared in Example 1 is composed of carbon and FeNi. Figure 1(b) and (c) show that the product has a distinct core-shell structure, with multiple layers of graphene sheets covering the core. The core and shell interplanar spacings were measured to show that the core interplanar spacing is about 0.206nm, which is close to the FeNi (111) interplanar spacing and consistent with the XRD data; while the shell interplanar spacing is about 0.35nm, which is close to the interplanar spacing of the graphene (002) plane, indicating that the shell is composed of multiple layers of graphene shells. The XRD diffraction peaks are high in intensity and sharp, proving that the prepared sample has a high degree of crystallinity.

[0065] Embodiment 5:

[0066] Using ferrocene and nickelocene as raw materials, the plasma reaction chamber was evacuated and then filled with nitrogen. After evacuation, argon was filled until the argon filled the entire reaction chamber to 10 5 Pa, isolated from air. The power of the first plasma generator was set to 4.5kW, the power of the second plasma generator was set to 4.5kW, the power of the third plasma generator was set to 4.5kW, and the total power was 13.5kW to excite stable ammonia plasma with ammonia. At this time, the effective reaction length of the airflow through the plasma was 30cm. The temperature of the ferrocene sublimation chamber was set to 130°C, and the temperature of the nickelocene sublimation chamber was set to 150°C. 2slpm of ammonia was introduced into the ferrocene fluidized bed, and 6slpm of ammonia was introduced into the nickelocene fluidized bed. The vapors of both were brought into the plasma flame. After the plasma reaction, carbon-coated nano-FeNi3 alloy powder was obtained. The XRD pattern of the product is shown in the figure. Figure 5 (a) shows the TEM image. Figure 5 As shown in (b) and (c).

[0067] Depend on Figure 5 As shown in (a), the product phase prepared in Example 1 is composed of carbon and FeNi3. Figure 5 (b) and (c) show that the prepared product has an obvious core-shell structure, with the core covered with multiple layers of graphene shell.

[0068] Embodiment 6:

[0069] Using ferrocene, nickelocene and cobaltocene as raw materials, the plasma reaction chamber was evacuated and filled with nitrogen, and then evacuated and filled with argon until the argon filled the entire reaction chamber to 10 5Pa, after isolating the air, setting the power of the reaction section, using ammonia as plasma to excite a stable ammonia plasma. The temperature of the ferrocene sublimation chamber is set to 130°C, the temperature of the nickelocene sublimation chamber is set to 150°C, and the temperature of the cobaltocene sublimation chamber is set to 60°C. Xslpm ammonia is introduced into the ferrocene fluidized bed, Yslpm ammonia is introduced into the nickelocene fluidized bed, and Zslpm ammonia is introduced into the cobaltocene fluidized bed. The vapors of the three are brought into the plasma flame, and carbon-coated nano-Fe is obtained through plasma reaction. X Ni Y Co Z Alloy powder.

[0070] Embodiment 7:

[0071] Using ferrocene, nickelocene, cobaltocene and manganocene as raw materials, the plasma reaction chamber was evacuated and filled with nitrogen, and then evacuated and filled with argon until the argon filled the entire reaction chamber to 10 5 Pa, after isolating the air, setting the power of the reaction section, using ammonia as plasma to excite a stable ammonia plasma. The temperature of the ferrocene sublimation chamber is set to 130°C, the temperature of the nickelocene sublimation chamber is set to 150°C, the temperature of the cobaltocene sublimation chamber is set to 60°C, and the temperature of the manganeseocene sublimation chamber is set to 120°C. Xslpm ammonia is introduced into the ferrocene fluidized bed, Yslpm ammonia is introduced into the nickelocene fluidized bed, Zslpm ammonia is introduced into the cobaltocene fluidized bed, and Pslpm ammonia is introduced into the manganeseocene fluidized bed. The vapors of the four are brought into the plasma flame, and carbon-coated nano-Fe is obtained through plasma reaction. X Ni Y Co Z Mn P Alloy powder.

[0072] The above embodiments are only for the purpose of facilitating those skilled in the art to understand the technical solution and are not intended to limit the present invention. Any modification or improvement based on the technical solution of the present invention shall fall within the protection scope of the present invention.

Claims

1. A multi-element nano alloy powder coated with a controllable carbon structure and adjustable composition, characterized in that: The multi-element nano alloy powder has a coating structure, wherein the coating layer is composed of carbon and has a thickness of 5-50nm; the core is a binary, ternary or quaternary alloy particle with controllable crystallinity and a particle size of 5-200nm, and is spherical or quasi-spherical.

2. The multi-element nano alloy powder according to claim 1, characterized in that: The magnetic core phase is represented by A, B, C, and D, respectively, representing Fe, Co, Ni, and Mn elements, and x, y, z, and p represent the molar fraction of each component. Its chemical formula is A x B y C z D p , where x+y+z+p=1, x,y,z,p≥0 and at least any two variables>0.

3. The multi-element nano alloy powder with controllable carbon structure and adjustable composition as claimed in claim 1, characterized in that: The carbon structure is one or both of amorphous carbon and graphite carbon.

4. A method for preparing a multi-component nano alloy powder coated with a controllable carbon structure and adjustable composition as claimed in claim 1, characterized in that: The following steps are involved: (1) After evacuating the plasma reaction chamber, fill it with nitrogen, and then evacuate it and fill it with argon until the argon fills the entire reaction chamber to 10 5 Pa, isolated from air; (2) introducing ammonia gas to adjust the ammonia partial pressure, and turning on the plasma generator power supply to excite and obtain a stable ammonia plasma flow; (3) subliming the metallocene compound in a plurality of sublimation chambers respectively; the temperature of the ferrocene sublimation chamber is set to 100-160° C., the temperature of the nickelocene sublimation chamber is set to 120-160° C., the temperature of the cobaltocene sublimation chamber is set to 40-100° C., and the temperature of the manganeseocene sublimation chamber is set to 110-150° C., and the carrier gas is ammonia; (4) introducing ammonia gas into the sublimation chamber respectively, and sending the metallocene compound vapor into the plasma region through the ammonia gas; (5) Adjusting the plasma generator power and the length of the plasma region; (6) the metallocene compound vapor and ammonia begin to react in a plasma reactor at a set power and zone length to generate carbon-coated nano-alloy powder; (7) The reaction chamber is cooled to room temperature under ammonia protection conditions, and the obtained powder is collected, which is the carbon-coated nano alloy powder.

5. The method according to claim 4, characterized in that The metallocene compound is ferrocene (C 10 H 10 Fe), nickelocene (C 10 H 10 Ni), cobalt cyclopentadienyl (C 10 H 10 Co) and manganese cyclopentadienyl (C 10 H 10 Mn) as a metal source and a carbon source.

6. The method according to claim 4, characterized in that The carrier gas flow rate Q is adjustable.

7. The method according to claim 4, characterized in that The plasma generator type includes one or more of inductively coupled plasma, microwave plasma, and capacitively coupled plasma. The generator power is adjustable and the plasma effective area in the reaction chamber is adjustable.

8. The method according to claim 4, characterized in that Plasma reaction regions of different lengths can be obtained by adjusting the lengths of inductive and capacitive plasma arc columns and the number of microwave plasma layers.

9. The method according to claim 4, characterized in that By controlling the flow rate of the carrier gas, the molar ratio of the metallocene compound entering the plasma reaction area per unit time is controlled, thereby controlling the core A x B y C z D p The content of each component in the alloy can be adjusted to achieve continuous adjustment of the alloy type and alloy composition.

Citation Information

Patent Citations

  • Method for preparing ferrum-nitrogen compound magnetic fluid with high-frequency plasma

    CN104851548A

  • Method for preparing graphene on surface of copper powder

    CN114572971A

  • Method

    CN104067425A

  • Preparation method for metal-clad carbon nano tube

    CN105642917A

  • Graphene-coated variable phase nano magnetic composite material and preparation method thereof

    CN106683813A